Analisis Efektivitas Keamanan Jaringan Layer 2: Port Security, VLAN Hopping, DHCP Snooping - Nurfaishal, Muhammad Dzaky; Akbar, Yuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
In the industrial era 4.0, which is marked by the rapid progress of computer networks and the internet, network security at Layer 2 is part of the Data Link Layer in the OSI model, which is very important considering the increasing number of cyber threats. This research aims to compare the effectiveness of various security algorithms applied to Layer 2 switches, namely MAC Address Filtering with Port Security, VLAN Hopping Mitigation, and DHCP Snooping. Some of these methods have the function or purpose of creating MAC address filtering, port limitations, VLAN protection, ARP, etc. The device used to conduct this research is a Cisco Switch. This research uses an experimental approach by implementing each method in different network scenarios and comparing it with external data, measuring effectiveness based on attack detection and prevention, as well as its impact on network performance, then combining several of these methods into one scope. The results show that each method has its own advantages and disadvantages, which function to block various types of attacks such as Flooding, Snooping, and Rogue DHCP. It is highly recommended to combine all security methods into one integrated system.